2017
DOI: 10.1136/bcr-2017-221498
|View full text |Cite
|
Sign up to set email alerts
|

Knotted urethral catheter: an unusual complication in adults

Abstract: Knotting of feeding tubes or urinary catheters has been reported as a rare complication in paediatrics when draining the bladder. This is caused by inserting thin flexible tubes too far in, allowing it to coil. We present a case of a 70-year-old woman who was catheterised during a routine spinal surgery, and the catheter coiled and balloon failed to deflate requiring a cystostopic approach to puncture the balloon and remove it. Awareness of this complication in female catheterisation and education on length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Mulawkar [6] reported knot formation in a 14-Fr straight urethral catheter during self-catheterization in a female adult patient. In both case reports, the authors suggested that the passage of an excessively long catheter might have caused catheter coiling and subsequent knotting in these female patients [5,6]. In women, it is unnecessary to fully insert the urethral catheter because the average length of the female urethra is 4 cm [5].…”
Section: To the Editormentioning
confidence: 99%
See 3 more Smart Citations
“…Mulawkar [6] reported knot formation in a 14-Fr straight urethral catheter during self-catheterization in a female adult patient. In both case reports, the authors suggested that the passage of an excessively long catheter might have caused catheter coiling and subsequent knotting in these female patients [5,6]. In women, it is unnecessary to fully insert the urethral catheter because the average length of the female urethra is 4 cm [5].…”
Section: To the Editormentioning
confidence: 99%
“…In both case reports, the authors suggested that the passage of an excessively long catheter might have caused catheter coiling and subsequent knotting in these female patients [5,6]. In women, it is unnecessary to fully insert the urethral catheter because the average length of the female urethra is 4 cm [5]. Therefore, we can usually confirm urine outflow within that depth.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations